2008
DOI: 10.1093/ajcn/87.5.1336
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation in human zinc absorption as influenced by dietary zinc and bioavailability

Abstract: Humans absorbed zinc more efficiently from low-zinc diets and adapted to further increase zinc absorption after consuming low-zinc, low-phytate diets for several weeks. Such adaptation did not occur with higher phytate diets. Zinc absorption can be predicted from dietary zinc and phytate after allowing for dietary equilibration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 26 publications
(57 reference statements)
4
73
2
1
Order By: Relevance
“…This fi nding is not unexpected as the diets of the women in both EPAs were low in zinc with high phytate-to-zinc molar ratios, and the inhibitory effect of phytate on zinc absorption in adults is now thought to be much larger than previously estimated [24] [32]. Moreover, there is no evidence of an adaptive response to habitual high phytate intakes on zinc absorption [33]. Nevertheless, the predicted risk of zinc defi ciency based on low plasma zinc concentrations was higher than predicted from zinc intakes.…”
Section: Zinc Statusmentioning
confidence: 81%
“…This fi nding is not unexpected as the diets of the women in both EPAs were low in zinc with high phytate-to-zinc molar ratios, and the inhibitory effect of phytate on zinc absorption in adults is now thought to be much larger than previously estimated [24] [32]. Moreover, there is no evidence of an adaptive response to habitual high phytate intakes on zinc absorption [33]. Nevertheless, the predicted risk of zinc defi ciency based on low plasma zinc concentrations was higher than predicted from zinc intakes.…”
Section: Zinc Statusmentioning
confidence: 81%
“…It is known that zinc absorption is affected by zinc status and that absorption efficiency is inversely correlated with the amount of ingested zinc [51]. Hunt et al showed that healthy humans, consuming low-zinc diets, increase zinc absorption, which was controlled by the ingested zinc dose [52]. This adaptation to zinc absorption is not possible after malabsorptive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For example, with only 900 mg phytate intake/d, the model predicts that it will require 100 mg ingested Zn to achieve this quantity of absorbed zinc (18). This model has also been used to develop recommendations for the zinc fortification of flour from a range of cereal grains (19); to predict the increase in absorbed zinc from a zinc-biofortified cereal (20,21); and to assist in the evaluation of data derived from experimental human studies in which quantities of ingested zinc and phytate were manipulated (22). The last research was also then used to evaluate this trivariate model, an evaluation that proved to be strongly supportive of the model in contrast to another purely mathematic model (23).…”
Section: Effect Of Dietary Phytate On the Bioavailability Of Ingestedmentioning
confidence: 99%
“…As additional total diet data are identified and new data are published that include phytate intake, these data have been added to the original data set of 21 to give a current total of 72 data sets (means) (Figure 2) (6,9,17,18,20,22,24). The parameters of the current model have been compared with the corresponding values for the original model ( Table 1) and indicate further improvement in the certainty of the estimates, which include a lower A MAX .…”
Section: Effect Of Dietary Phytate On the Bioavailability Of Ingestedmentioning
confidence: 99%